Mycosis fungoides: improving the diagnostics of early and late stages by quantifying the results of immunohistochemical studies of skin biopsy - I. A. Kuklin; M. M. Kokhan; G. D. Safonova; N. P. Toropova; I. D. Kuznetsov (Лечащий Врач)
The data of Immunohistochemical and Morphometric studies of skin biopsy images of 30 patients with I, II and III stages of Mycosis Fungoides were analyzed. Diagnostically relevant threshold values of the volume fraction of positive staining cells of the dermal infiltrate with MCA CD3, CD4, CD8 and Ki67 were evaluated. These data allow to build a mathematical model which allows effectively to distinguish between early (I-IIA) and late (IIB-III) stages of Mycosis Fungoides. Clinical examples of use of this model are given.